Динамiка пробної нуль-струни, без обертання, в гравiтацiйному полi “розмазаної” замкненої нуль-струни, яка прямує в площинi z = 0 - Lelyakov, O. P.; Karpenko, A. S.; Babadzhan, R.-D. O. (Publishing house "Academperiodika", 2018)
The dynamics of a test null string moving in the gravitational field of a closed “thick” null string radially expanding or collapsing in the plane z = 0 is considered, provided that the former string does not rotate initially.